Pengaruh Pergaulan Teman Sebaya dan Tayangan Kekerasan Media Sosial terhadap Perilaku Agresif Siswa di SMP Negeri 3 Lubuk Sikaping - Sartika, Dewi; Syawaluddin, Syawaluddin (Lembaga Yasin AlSys, 2023)
Things that influence students' aggressive behavior at school are peer association and viewing of violence on social media. The aims of the research are (1) to find out how much influence peer association partially has on students' aggressive behavior (2) to find out how much influence social media violence shows partially on student aggressive behavior (3) find out how much influence peer association and social media violence shows simultaneously to the aggressive behavior of students. Associative type quantitative research methods. The research population for class IX students at SMPN 3 Lubuk Attitude is 120 students. The sampling technique used the Proportional Random Sampling technique and obtained a sample of 92 students. The research instruments were the peer association scale, the scale of social media violence broadcasts and the aggressive behavior scale which were compiled and developed by the researchers themselves. Data analysis is descriptive analysis, hypothesis testing using simple linear regression and multiple linear regression. The results showed that: (1) There is a positive and significant influence of peer association (X1) partially on aggressive behavior of students (Y) with a significant value of 0.008 <0.05; (2) There is a positive and significant effect of the social media violence display variable (X2) partially on the aggressive behavior of students (Y) with a significant value of 0.000 <0.05; (3) There is a positive influence between peer association variables (X1) and social media violence shows (X2) together on aggressive behavior of students (Y) with a significance value of 0.000 <0.05.